APLICATION OF FINITE ELEMENT METHOD IN HYDROTHERMAL SYSTEM MODELING - CAMAR REMOA (NIM : 10209020),
The Finite Element Method (FEM) is one numerical method for finished the problematical of limite condition in diferensial equation. The FEM contents is general domain representation in a simple sub-domain point of view, called as finite element. This method has been applicated in groundwater current modeling and SP (Self Potential) distribution in 2D profile. Validation of SP distribution has been compared to SP values in the field.Result of this modeling is hydrothermal velocity flows about 10-11 - 10-7 m/second and we can see the manifestation formed in Domas Carter. The SP values distribution modeling has been bigger from Domas Crater to Jarian Crater.